Preclinical Toxicological Assessment of A Novel siRNA, SLN360, Targeting Elevated Lipoprotein (a) in Cardiovascular Disease. (23rd June 2022) - Rider, David; Chivers, Simon; Aretz, Julia; Eisermann, Mona; Löffler, Kathrin; Hauptmann, Judith; Morrison, Eliot; Campion, Giles
Abstract: SLN360 is a liver-targeted N-acetyl galactosamine (GalNAc)-conjugated small interfering RNA (siRNA) with a promising profile for addressing lipoprotein (a)-related cardiovascular risk. Here, we describe the findings from key preclinical safety studies. In vitro, SLN360 specifically reduced LPA expression in primary human hepatocytes with no relevant off-target effects. In rats, 10 mg/kg subcutaneous SLN360 was distributed specifically to the liver and kidney (peak 126 or 246 mg/g tissue at 6 h, respectively), with <1% of peak liver levels observed in all other tested organs. In vitro, no genotoxicity and no effect on human Ether-a-go-go Related Gene currents or proinflammatory cytokine production was observed, whereas in vivo, no SLN360-specific antibodies were detected in rabbit serum. In rat and nonhuman primate 29-day toxicology studies, SLN360 was well tolerated at all doses. In both species, known GalNAc-conjugated siRNA-induced microscopic changes were observed in the kidney and liver, with small increases in alanine aminotransferase and alkaline phosphatase observed in the high dose rats. Findings were in line with previously described siRNA-GalNAc platform-related effects and all observations were reversible and considered nonadverse. In cynomolgus monkeys, liver LPA messenger RNA and serum lipoprotein (a) were significantly reduced at day 30 and after an 8-week recovery period. No dose-related changes in safety assessment endpoints were noted. No SLN360-induced cytokine production, complement activation, or micronucleus formation was observed in vivo . The toxicological profile of SLN360 presented here is restricted to known GalNAc siRNA effects and no other toxicity associated with SLN360 has been noted. The preclinical profile of SLN360 confirmed suitability for entry into clinical studies.